Basics of Health Care Team Relationships and Interprofessional Practice - Koloroutis, Mary (2019)
Relationship-based care is a philosophy, an operational plan for excellence and a way of being. It is essential that the transformation of a health care organization be a team effort based on a common vision, values ​​and anticipated results. Keywords: Relationships, Health Care Team, Interprofessional Practice